A review on mechanism and application of functional coatings for overhead transmission lines - Tao, Bo; Cheng, Li; Wang, Jiuyi; Zhang, Xinlong; Liao, Ruijin (Frontiers in Materials, 2022)
Overhead transmission line is the main method of power transmission. Conductors, insulators, and towers are the primary electrical equipment of overhead transmission lines. Due to overhead transmission lines work in the natural environment, problems such as icing, corona discharge, contamination deposition, and corrosion will arise. As a result, some accidents may occur, which cause enormous economic losses. The above problems can be solved by coating functional coatings with superhydrophobic, semiconductive, anti-corrosion, and other characteristics on electrical equipment, which has the advantages of low cost and high efficiency. Therefore, functional coatings have become a research hotspot in the field of external insulation in recent years. In view of the various problems of different electrical equipment in overhead transmission lines, distinctive solutions need to be adopted, so this review classifies the coatings according to the usage scenarios and functions. In each category, first briefly outlines the causes of the electrical equipment problem, then introduces the mechanism of using this type of functional coating to solve the problem, next summarizes the development and application status of this type of coating, after summarizes the limitations of this coating, and finally provides a summary of the key issues in the research of functional coatings and gives an outlook on potential future research directions. This review intends to provide readers with a comprehensive overview of the performance principles and current application status of functional coatings for overhead transmission lines.